PERCEPTION AND COMMUNICATION IN MANAGING PANDEMIC COVID 19 AMONG ROYAL MALAY REGIMENT - Nora Ibrahim, Jessica Ong Hai Liaw, Inderjit Singh Tara Singh, Rayyan Cheong Tian Ming, Noor Azmi MohdZainol,Safar Yaacob, Abdul Hamid Moiden&NorashikinSahol Hamid (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the last several years, a virus known as the coronavirus has been a problem for the whole world. Coronavirus is a specific type of virus that can cause infections in the respiratory tract and has a deadly outcome. Coronavirus 2019, a coronavirus discovered in China, is spreading (COVID-19). The efficacy of these mitigation measures is primarily contingent on personnel of the Royal Malay Regiment's cooperation and compliance. Personnel attitudes on health issues are extremely important in changing people's behaviour. This research seeks to determine the perception and communications align with the Royal Malay Regiment's efforts to this COVID-19. Utilizing 249 respondents from the Royal Malay Regiment, this correlational study design was conducted using questionnaires, and the Statistical Package for the Social Sciences 25.0 and Smart PLS 3.3.2 were used to analyse the results. The research results proved that accurate perception and communication skills play a vital role in regulating the COVID-19 pandemic. This study's findings can help commanding officers by supplying the necessary guidance in planning to boost their soldiers' skill in working through the hard missions that are to come. Most personnel think that they need to understand how to effectively communicate in an emergency, and to do so, it's crucial to educate the soldiers and help them become more alert